(untitled) (Revista de Ensino em Artes, Moda e Design, 2020)
In the present work, we present the compilation of an interview conducted by a professor of Higher Education (UFRPE) to another co-worker (Unisinos), the interviewee who reflects and discusses issues related to Participatory Design (PD). The path of conversation traced by the professionals covers not only the educational scope but that of everyday life, that is, it also deals with how Participatory Design can be considered pragmatically for the development and / or monitoring of practical activities concerning and arising from other dimensions of everyday life of the social subject. In the course of the construction of thought proposed, terms such as curiosity, proactivity, independence, autonomy, and collectivity were quite recurrent to rethink pedagogical and professional practices that are not restricted to Design, as they are necessary for any activities that intend that everyone who is in them involved participating. During the interview, it was verified how the adoption of the participatory design concepts presents itself as a challenging practice, both in the educational field and in the perspective of its performance in other fields of knowledge. Finally, it should be noted that, about the technical aspects of the interview, it was conducted through the Jitsi Meet video conference platform, and lasted approximately 40 minutes, recorded via an audio application, available for Android system - and, subsequently, it was transcribed and organized according to the norms of the language, having its approval for publication by the interviewed teacher.